2023
DOI: 10.3390/tropicalmed8040235
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Qualitative Evidence on Malaria in Pregnancy, 2005–2022: A Systematic Review

Abstract: Qualitative research on malaria in pregnancy (MiP) is incipient, therefore its contextual, experiential and symbolic associated factors are unknown. This study systematizes the qualitative research on MiP, describes knowledge, perceptions and behaviors about MiP, and compiles individual, socioeconomic, cultural and health system determinants of MiP through a meta-synthesis in 10 databases. A total of 48 studies were included with 2600 pregnant women, 1300 healthcare workers, and 2200 relatives or community mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…This situation has also been described in the qualitative component of mixed studies on MiP, and a systematic review of QHR in MiP that reported lacking knowledge about MiP and its consequences, lacking perception of the risk of becoming infected, and poor knowledge about prevention [ 6 , 7 ]. This demonstrates multiple challenges for health education, information and communication programmes, since the individual cognitive dimension in this population is determined by social, cultural and economic processes, which are excluded in this type of health strategy, despite having a greater explanatory power on individual behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This situation has also been described in the qualitative component of mixed studies on MiP, and a systematic review of QHR in MiP that reported lacking knowledge about MiP and its consequences, lacking perception of the risk of becoming infected, and poor knowledge about prevention [ 6 , 7 ]. This demonstrates multiple challenges for health education, information and communication programmes, since the individual cognitive dimension in this population is determined by social, cultural and economic processes, which are excluded in this type of health strategy, despite having a greater explanatory power on individual behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Singular level findings were determined by the economic, geographic, cultural and health system barriers to access malaria control programmes, in interaction with a lacking perception of the risk of becoming ill and dying for this disease. These events have been recurrent in the QHR on MiP, and in other countries they have been used to explain less effectiveness of control strategies (such as intermittent preventive treatment, use of nets, detection and treatment of cases) [ 7 , 25 ]. These barriers coexist and would explain the high frequency of asymptomatic MiP, which increases the risk of severe malaria, placental malaria, congenital malaria, anaemia, and low birth weight, among other outcomes [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations